2017
DOI: 10.1051/0004-6361/201730735
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically aligned dust and SiO maser polarisation in the envelope of the red supergiant VY Canis Majoris

Abstract: Aims. Polarization observations of circumstellar dust and molecular (thermal and maser) lines provide unique information about dust properties and magnetic fields in circumstellar envelopes of evolved stars. Methods. We use Atacama Large Millimeter/submillimeter Array Band 5 science verification observations of the red supergiant VY CMa to study the polarization of SiO thermal/masers lines and dust continuum at ∼ 1.7 mm wavelength. We analyse both linear and circular polarization and derive the magnetic field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
2
43
1
Order By: Relevance
“…Very-long-baseline interferometry (VLBI) observations have shown that SiO masers orient themselves in a ring-like structure around the central stellar object. The polarization of these SiO masers, irrespective of their angular momentum transition, show well-ordered polarization vectors with respect to this structure (Kemball & Diamond 1997;Cotton et al 2004;Plambeck et al 2003;Vlemmings et al 2011bVlemmings et al , 2017. This is taken to be an indicator of an ordered magnetic field.…”
Section: Sio Maser Polarization Observationsmentioning
confidence: 90%
“…Very-long-baseline interferometry (VLBI) observations have shown that SiO masers orient themselves in a ring-like structure around the central stellar object. The polarization of these SiO masers, irrespective of their angular momentum transition, show well-ordered polarization vectors with respect to this structure (Kemball & Diamond 1997;Cotton et al 2004;Plambeck et al 2003;Vlemmings et al 2011bVlemmings et al , 2017. This is taken to be an indicator of an ordered magnetic field.…”
Section: Sio Maser Polarization Observationsmentioning
confidence: 90%
“…′′ 5 from the star with the brightest (Clump C) having a total mass of at least 2.5 × 10 −3 M ⊙ (O'Gorman et al 2015). More recent ALMA measurements of Clump C yield a dust mass alone of > 1.2 × 10 −3 M ⊙ , implying a total mass of ∼ 0.1 M ⊙ (Vlemmings et al 2017). These measurements imply short term, high mass loss in separate events over several hundred years.…”
mentioning
confidence: 94%
“…The presence of magnetic fields is supported by the Zeeman splitting and polarization of the masers in its circumstellar ejecta (Vlemmings et al 2002(Vlemmings et al , 2003(Vlemmings et al , 2005Shinnaga et al 2017). Recent ALMA continuum observations (Vlemmings et al 2017) reveal polarized dust emission from magnetically aligned gains within 0. ′′ 5 of the star.…”
mentioning
confidence: 99%
“…It is difficult to directly observe magnetic fields; one typically has to use the polarization properties of the observed light (e.g., Han 2017). For (sub)millimeter interferometers, such as ALMA, magnetic field detection is done mostly through dust (e.g., Hull et al 2017) and line polarization observations (e.g., Vlemmings et al 2017). However, it has recently become increasingly clear that dust polarization does not always faithfully trace the magnetic field morphology, but instead it can be affected by processes such as self-scattering (Kataoka et al 2015(Kataoka et al , 2017.…”
Section: Introductionmentioning
confidence: 99%